A high-efficiency carbon-forming anti-drip flame retardant and its preparation method and application
By grafting unsaturated conjugated cross-linkable molecules containing benzene rings on a single layer of α-zirconium phosphate, a highly efficient carbon-forming anti-drip flame retardant is formed, which solves the problem of insufficient flame retardant and anti-drip properties of existing polymer materials. An ideal problem to achieve efficient flame retardancy, droplet resistance and improved mechanical properties while being environmentally friendly.
Patent Information
- Application Number
- CN202411095389.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-12
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-08-12
AI Technical Summary
The flame retardant and droplet resistance of existing polymer materials is not ideal, especially when processing at high temperatures, the increase in the amount of flame retardant will lead to a decrease in the spinning ability of the fibers, and simple organic flame retardant in polymer materials The role in this paper is limited and needs to be combined with inorganic flame retardant, resulting in deterioration of mechanical properties.
A monolayer α-zirconium phosphate with an aspect ratio greater than 500 and surface-grafted unsaturated conjugated cross-linkable molecules containing benzene rings is used as a high-efficiency carbon-forming anti-melting droplet flame retardant. Unsaturated conjugated cross-linkable molecules are grafted on a single layer of α-zirconium phosphate to form an organic-inorganic hybrid structure to improve flame retardant properties.
It achieves efficient char formation, improved flame retardancy and droplet resistance, and at the same time enhances the mechanical properties of the fiber. Only a small amount of flame retardant is added to achieve good results, and the α-zirconium phosphate used is environmentally friendly.
Smart Images

Figure CN118639341B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of textile and polymer materials, and relates to a high-efficiency charring and anti-melting-drip flame retardant and a preparation method and application thereof. Background Art
[0002] The application of polymer materials is becoming more and more extensive, and has spread to all aspects of people's production and life. It is one of the indispensable materials in human production activities. However, polymer materials are flammable, which also poses a serious threat to people's life and property safety. At the same time, polymer materials are usually accompanied by serious dripping during the combustion process. The dripping of molten metal on the human body will cause serious burns, and dripping on other flammable materials will cause secondary ignition. Therefore, the anti-drip of polymer combustion is also a focus of people's attention. Chemical fibers, especially melt-spun fibers, have the particularity of molding and processing, and the flame retardant and anti-drip properties of fibers are not ideal at present. There are mainly the following problems: 1. The processing of melt-spun fibers needs to be carried out at high temperatures, so the flame retardant must first meet the thermal stability at the melt-spun fiber processing temperature; 2. If you want to achieve a good flame retardant effect, you must increase the amount of flame retardant added. However, the increase in the flame retardant content will lead to a decrease in the spinnability of the fiber; 3. The flame retardant and anti-melting droplet effect of pure organic flame retardants in polymer materials is limited, and it is often necessary to use it in combination with inorganic flame retardants to improve the flame retardant properties. The compatibility problem of inorganic flame retardants will lead to the deterioration of the mechanical properties of the fiber. Therefore, the preparation of fiber materials with high-efficiency flame retardancy, anti-melting droplet properties, good spinnability and good mechanical properties has important application value and social value.
[0003] In the existing reports on flame retardant and anti-melting droplet fibers, there are mainly the following categories: 1. Copolymerization, introducing flame retardant and anti-melting droplet units into the molecular chain of polymer materials, such as patent CN117512802A and patent CN116813909A. Copolymerization has high requirements on reaction equipment, and current polymerization equipment often cannot meet them. At the same time, the introduction of flame retardant functional units will seriously destroy the regularity of polymer molecular chains, thereby affecting the crystallinity of polymer materials, and further affecting subsequent molding processing; 2. Post-finishing, immersing fabrics or fabrics in a dispersion containing flame retardants, and then grafting and curing by irradiation, etc., such as CN116427173A. The flame retardant fabrics or fabrics obtained by post-finishing have flame retardant properties. Compared with other methods, its durability is much worse, and it will also affect the air permeability of the fabric, and its usage scenarios are very limited; 3. Blending, flame retardant masterbatch and polymer matrix are melt-spinned to obtain flame retardant and anti-drip fibers. Usually, the amount of flame retardant added is relatively high. For example, the content of flame retardant in the fiber of CN116693859A and CN116770453A is 5%~10%. At this amount of addition, the fiber is difficult to shape and process. At the same time, the raw materials used are mostly POSS structures, which are expensive and difficult to apply industrially. Although CN117210956A obtains flame retardant fibers at a lower flame retardant addition, the flame retardant used is a halogen flame retardant. With the strengthening of environmental awareness, halogen flame retardants are gradually banned.
[0004] Therefore, there is still a wide demand for more excellent flame retardant and anti-drip fibers. Summary of the invention
[0005] The purpose of the present invention is to solve the problems existing in the prior art and to provide a high-efficiency char-forming anti-drip flame retardant and a preparation method and application thereof.
[0006] To achieve the above object, the technical solution adopted by the present invention is as follows:
[0007] A highly efficient char-forming anti-melting dripping flame retardant, which is a monolayer α-zirconium phosphate with a surface grafted with unsaturated conjugated cross-linkable molecules containing benzene rings and a width-to-thickness ratio greater than 500;
[0008] The structural formula of the unsaturated conjugated cross-linkable molecule containing a benzene ring is as follows:
[0009] or ;
[0010] In the formula, -R- is -CH=CH-, -C≡C-, -CH=N- or -N=N-; at least one of -R1 to -R6 is an active functional group, which is -NH2, -COOH or -SO3H, and the rest are -H.
[0011] As the preferred technical solution:
[0012] As described above, in the highly efficient carbon-forming anti-dripping flame retardant, the grafting rate of the unsaturated conjugated cross-linkable molecules containing benzene rings on the monolayer α-zirconium phosphate is 30-60wt%.
[0013] As described above, the high-efficiency charring anti-dripping flame retardant has an initial thermal decomposition temperature of >300°C, and an exothermic peak appears between 350°C and 400°C on the DSC test curve (indicating that the unsaturated conjugated cross-linkable molecules containing benzene rings undergo a cross-linking reaction).
[0014] The present invention also provides a method for preparing a highly efficient charring anti-dripping flame retardant as described in any of the preceding items, by grafting unsaturated conjugated cross-linkable molecules containing benzene rings onto a monolithic α-zirconium phosphate using a silane coupling agent to obtain a highly efficient charring anti-dripping flame retardant.
[0015] As the preferred technical solution:
[0016] In the method described above, the silane coupling agent is γ-aminopropyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane, γ-aminopropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane or γ-glycidyloxypropyltriethoxysilane.
[0017] The method described above has the following specific steps:
[0018] (1) using a stripping agent to strip the layered α-zirconium phosphate in a solvent to obtain a paste consisting of a single layer of α-zirconium phosphate and a solvent;
[0019] (2) Add the ethanol solution of the silane coupling agent dropwise to the paste. After the addition is complete, react under stirring at 0.1 MPa and 25-80°C for 12-24 hours. After post-treatment (filtration, washing with anhydrous ethanol for 3 times, and vacuum drying at 60°C for 24 hours), a white solid powder is obtained.
[0020] (3) The solid powder is dispersed in an organic solvent to obtain a dispersion, and an unsaturated conjugated cross-linkable molecular solution containing a benzene ring and a catalyst are added to the dispersion. The dispersion is reacted at 0.1-0.15 MPa and 25-120° C. for 3-12 hours. After post-treatment (filtration, washing, and drying), a highly efficient carbon-forming anti-dripping flame retardant is obtained.
[0021] In the above method, step (1) is specifically as follows:
[0022] (1.1) Add the stripping agent solution dropwise into the layered α-zirconium phosphate dispersion at a dropping speed of 1 to 2 seconds per drop, accompanied by mechanical stirring and ultrasound, and continue to react until the pH value reaches 7 to 8 after the dropping is completed;
[0023] The stripping agent is one or more of D-aminopropanol, 4-amino-1-butanol, 2-aminocyclohexanol, 6-amino-1-hexanol, 3-aminobutanol, 3-amino-1,2-propylene glycol, tromethamine, tetrabutylammonium hydroxide, and hexadecyltrimethylammonium hydroxide;
[0024] The concentration of the stripping agent solution is 10wt%, and the solvent is deionized water;
[0025] The average particle size of the layered α-zirconium phosphate is 2 μm, which ensures that a single layer of α-zirconium phosphate with a large width-to-thickness ratio can be obtained after stripping and modification, and is also beneficial for subsequent spinning processing;
[0026] The concentration of the layered α-zirconium phosphate dispersion is 10-15 wt % to prevent gelation during the stripping and modification process, and the solvent is deionized water;
[0027] The mass ratio of layered α-zirconium phosphate to stripping agent is 1:0.6~0.8;
[0028] (1.2) Use an acid solution to adjust the pH value of the reaction system to 2-3 to ensure that the stripping agent is completely free in the solvent, centrifuge (speed of 6000-10000 r / min), remove the upper layer of liquid, and obtain a translucent paste-like liquid;
[0029] The acid solution is a hydrochloric acid aqueous solution, a nitric acid aqueous solution or a phosphoric acid aqueous solution;
[0030] (1.3) After adding deionized water to the translucent paste liquid, stir, centrifuge, remove the upper liquid, repeat the above operation three times and then perform rotary evaporation to obtain a paste with a water content of 10~15wt%.
[0031] In the method described above, in step (2), the concentration of the ethanol solution of the silane coupling agent is 10wt%, and the mass of the silane coupling agent is 30-50% of the mass of the layered α-zirconium phosphate. Controlling the amount of the silane coupling agent in this way can ensure a high grafting rate of the subsequent unsaturated conjugated cross-linkable molecules containing benzene rings, and can also avoid affecting the width-to-thickness ratio of the monolithic α-zirconium phosphate.
[0032] In the method as described above, in step (3), the concentration of the dispersion is 8-10 wt %, and the organic solvent is toluene, dichloromethane, chloroform, acetone, dimethyl sulfoxide or DMF (dimethylacetamide);
[0033] The concentration of the solution of the unsaturated conjugated crosslinkable molecule containing a benzene ring is 10-20wt%, the solvent is toluene, dichloromethane, chloroform, acetone, dimethyl sulfoxide or DMF, and the mass of the unsaturated conjugated crosslinkable molecule containing a benzene ring is 30-60% of the mass of the layered α-zirconium phosphate;
[0034] The catalyst is azobisisobutyronitrile, 1,3-dicyclohexylcarbodiimide or p-toluenesulfonic acid, and the mass of the catalyst is 0.05-0.1% of the mass of the unsaturated conjugated cross-linkable molecule containing a benzene ring.
[0035] The present invention also provides a highly efficient carbon-forming anti-melting-drip flame-retardant fiber, which is composed of a polymer matrix and a highly efficient carbon-forming anti-melting-drip flame retardant as described in any of the preceding items dispersed therein;
[0036] The monolayer α-zirconium phosphate in the high-efficiency char-forming anti-drip flame retardant is oriented along the axial direction of the fiber.
[0037] As the preferred technical solution:
[0038] The high-efficiency carbonized anti-melting droplet flame-retardant fiber as described above, wherein the polymer matrix is polyester; the content of the high-efficiency carbonized anti-melting droplet flame retardant in the high-efficiency carbonized anti-melting droplet flame-retardant fiber is 1-3wt%, the LOI of the high-efficiency carbonized anti-melting droplet flame-retardant fiber is greater than 32%, and the UL-94 reaches V0 grade;
[0039] Alternatively, the polymer matrix is polyamide; the content of the high-efficiency charring anti-melting droplet flame retardant in the high-efficiency charring anti-melting droplet flame retardant fiber is 1-3wt%, the LOI of the high-efficiency charring anti-melting droplet flame retardant fiber is greater than 32%, and the UL-94 reaches V0 grade.
[0040] The present invention also provides a method for preparing a high-efficiency charring anti-melting droplet flame-retardant fiber as described above, wherein the flame-retardant slices are melt-spun, and four pairs of drawing rollers are used for drawing during the melt spinning process. The temperature of the first pair of drawing rollers is 80~120°C, the temperature of the second pair of drawing rollers is 130~150°C, the temperature of the third pair of drawing rollers is 180~200°C, the temperature of the fourth pair of drawing rollers is 200~240°C, and the total drawing multiple is 4.5~5.0, so as to obtain a high-efficiency charring anti-melting droplet flame-retardant fiber.
[0041] The present invention can make the monolayer α-zirconium phosphate in the high-efficiency charring anti-drip flame retardant oriented along the axial direction of the fiber, because: ① the width-to-thickness ratio of the high-efficiency charring anti-drip flame retardant is greater than 500; ② the total stretching multiple and the temperature of the four pairs of stretching rollers can ensure that the monolayer α-zirconium phosphate randomly dispersed in the fiber can be fully oriented under the induction of stretching to form an orderly oriented arrangement structure.
[0042] As the preferred technical solution:
[0043] According to the method described above, the spinning speed of the first pair of drafting rollers is 600~700m / min, the spinning speed of the second pair of drafting rollers is 2.0~2.5 times the spinning speed of the first pair of drafting rollers, the spinning speed of the third pair of drafting rollers is 1.3~1.5 times the spinning speed of the second pair of drafting rollers, and the spinning speed of the fourth pair of drafting rollers is 1.0~1.2 times the spinning speed of the third pair of drafting rollers.
[0044] According to the method described above, the preparation process of the flame retardant slice is as follows: first, the high-efficiency charring anti-drip flame retardant and the polymer powder are melt-blended to obtain the flame retardant slice, the polymer powder and the polymer slice are made of the same material, and the prepared flame retardant slice has a tensile breaking strength of 54.2~85.7MPa and a complex viscosity of 182~225Pa·s at 370°C.
[0045] Principle of the invention:
[0046] The high-efficiency carbonization and anti-melting-drip flame-retardant fiber of the present invention has the characteristics of high-efficiency carbonization, flame retardancy and anti-melting-drip, and the reason is that:
[0047] (1) The stripped α-zirconium phosphate is a monolayer structure, with a thickness of about 1 to 4 nm, a surface width of about 2 μm, and a width-to-thickness ratio of about 1000 to 2000 after stripping. After surface grafting of unsaturated conjugated crosslinkable molecules containing benzene rings, the width-to-thickness ratio is still greater than 500. After the flame retardant is blended and extruded with a polymer matrix, the monolayer α-zirconium phosphate coated with unsaturated conjugated crosslinkable molecules containing benzene rings is randomly dispersed in the melt / fiber before being drawn; during the fiber drawing process, after the melt is extruded from the spinneret hole and drawn four times, the monolayer α-zirconium phosphate is induced by the four drawing actions to change from the original disordered dispersion to a directional distribution after being oriented along the axial direction of the fiber, which can better exert its flame retardant function, while the unstripped α-zirconium phosphate does not have this feature.
[0048] (2) After stripping, the P-OH of the α-zirconium phosphate is completely exposed, which can provide more reaction binding sites and increase the grafting rate of unsaturated conjugated cross-linkable molecules containing benzene rings. The grafting rate can reach 30-60%, so that the outside of the monolithic α-zirconium phosphate is coated with organic molecules to form an organic-inorganic hybrid structure, which is conducive to its better dispersion in the polymer matrix. At the same time, the flame retardant contains unsaturated conjugated units with benzene rings, which have a high carbon content and are grafted on the surface of the monolithic α-zirconium phosphate, providing a rich carbon source for promoting carbonization under the action of the P element, which is conducive to carbonization and improves the flame retardant and smoke suppression functions.
[0049] (3) After the unsaturated conjugated unit is introduced, it undergoes a self-crosslinking reaction at high temperature (above 350°C). At this time, each single-layer α-zirconium phosphate is cross-linked with each other through the surface-grafted cross-linkable molecules, which can greatly increase the viscosity of the melt and reduce the fluidity of the melt at high temperature, so that the melt will not drip during the combustion process. Under the synergistic effect of the flame retardant, a continuous and dense carbon layer is formed by relying on the directional distribution of the cross-linked sheet zirconium phosphate and the cross-linking reaction on the surface at high temperature. Even if the fiber is ignited, the fiber will burn without dripping due to the synergistic effect between the sheet zirconium phosphate, the benzene ring conjugated structure, and the cross-linkable group. At the same time, the fiber can be self-extinguishing by quickly forming a continuous and dense carbon layer.
[0050] In addition, due to the directional arrangement of the monolithic α-zirconium phosphate in the fiber, the mechanical properties of the fiber itself can be enhanced.
[0051] Beneficial effects:
[0052] (1) The stripped α-zirconium phosphate of the present invention has a monolithic structure, and after being surface-grafted with unsaturated conjugated cross-linkable molecules containing benzene rings, the aspect ratio is still greater than 500. During the fiber drawing process, the melt is extruded from the spinneret hole and after four drawing steps, the monolithic α-zirconium phosphate is induced by the four drawing steps to change from the original disordered dispersion to oriented distribution along the axial direction of the fiber, which can better exert its flame retardant function; in addition, due to the oriented arrangement of the monolithic α-zirconium phosphate in the fiber, the mechanical properties of the fiber itself can also be enhanced.
[0053] (2) The high-efficiency charring anti-dripping flame retardant prepared by the present invention only needs to be added in a small amount to achieve anti-dripping performance and better flame retardant performance, that is, the content of the high-efficiency charring anti-dripping flame retardant in the high-efficiency charring anti-dripping flame retardant fiber is only 1-3wt%; and when preparing the high-efficiency charring anti-dripping flame retardant, α-zirconium phosphate is selected as the inorganic flame retardant, which is more environmentally friendly than traditional halogen flame retardants; and the high-efficiency charring anti-dripping flame retardant prepared by the present invention only needs to be added.
[0054] (3) The flame retardant of the present invention contains an unsaturated conjugated unit with a benzene ring, which has a high carbon content and is grafted on the surface of a monolithic α-zirconium phosphate, providing a rich carbon source for promoting carbonization under the action of the P element, which is beneficial to carbonization and improves the flame retardant and smoke suppression functions.
[0055] (4) Unsaturated conjugated units are introduced into the high-efficiency char-forming anti-drip flame retardant prepared by the present invention, which undergoes a self-crosslinking reaction at high temperature (above 350°C), which can greatly increase the viscosity of the melt and reduce the fluidity of the melt at high temperature, so that the melt will not drip during the combustion process. Under the synergistic effect of the flame retardant, a continuous and dense carbon layer is formed by relying on the directional distribution of the cross-linked lamellar zirconium phosphate and the cross-linking reaction occurring on the surface at high temperature. BRIEF DESCRIPTION OF THE DRAWINGS
[0056] Figure 1 This is a graph showing the change in complex viscosity of polyester and flame retardant chips with temperature in Example 1 of the present invention;
[0057] Figure 2 This is a TEM image of the high-efficiency carbon-forming anti-droplet flame-retardant fiber of Example 1 of the present invention. DETAILED DESCRIPTION
[0058] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0059] The testing methods of the relevant performance indicators in the following embodiments and comparative examples are as follows:
[0060] Grafting rate: The flame retardant fiber was measured using a thermogravimetric analyzer.
[0061] Initial thermal decomposition temperature: The flame retardant fiber was measured using a thermogravimetric analyzer. The heating rate during the test was 10°C / min. The test temperature range was 30~700°C. The temperature at which the thermal weight loss was 5wt% was the initial thermal decomposition temperature.
[0062] DSC test: Differential scanning calorimeter is used to measure the flame retardant fiber. The heating rate during the test is 10℃ / min and the test temperature range is 30~600℃.
[0063] LOI: The flame retardant fiber is tested in accordance with GB / T 2406.2-2009. An oxygen index tester is used for the test. The top surface ignition method A is used to ignite the sample.
[0064] UL-94: The flame retardant fiber is tested according to the test method B-vertical burning test in the GB / T 2408-2008 standard, and a vertical burning tester is used for the test.
[0065] Complex viscosity: The flame retardant and anti-drip plastic products are measured using a rotational rheometer; the mode is a variable temperature mode, and the test temperature range is 300~400℃.
[0066] Tensile breaking strength of polymer slices and flame retardant slices: polymer slices and flame retardant slices were tested according to the standard of GB / T 1040.2-2006.
[0067] Example 1
[0068] A method for preparing a highly efficient carbonized anti-melting droplet flame-retardant fiber, the specific steps are as follows:
[0069] (1) Preparation of raw materials;
[0070] Stripping agent solution: the solute is D-aminopropanol, the solvent is deionized water, and the concentration is 10wt%;
[0071] Layered α-zirconium phosphate dispersion: The dispersed phase is layered α-zirconium phosphate (manufacturer is Shanghai Runhe Nanomaterial Technology Co., Ltd., brand name is RHA-ZR, average particle size is 2μm), the dispersion medium is deionized water, and the concentration is 10wt%;
[0072] Acid solution: hydrochloric acid aqueous solution, concentration is 1 mol / L;
[0073] Deionized water;
[0074] Ethanol solution of silane coupling agent: the solute is γ-aminopropyltriethoxysilane, the concentration is 10wt%;
[0075] Organic solvent: toluene;
[0076] Unsaturated conjugated cross-linkable molecular solution containing benzene ring: the solute is 4-phenylethynylphthalic anhydride, the solvent is toluene, and the concentration is 10wt%;
[0077] Catalyst: 1,3-dicyclohexylcarbodiimide;
[0078] Polymer chips: polyester, manufactured by Sinopec, brand FG600, tensile strength at break 52.6MPa;
[0079] Polymer powder: The polymer slices are pulverized by a high-speed pulverizer at a speed of 35000r / min for 2min to obtain polymer powder;
[0080] (2) Preparation of highly efficient carbon-forming anti-drip flame retardant;
[0081] (2.1) adding the stripping agent solution dropwise to the layered α-zirconium phosphate dispersion at a dropping speed of 1 second / drop, accompanied by mechanical stirring and ultrasound, and continuing to react after the dropping is completed until the pH value is 7; wherein the mass ratio of the layered α-zirconium phosphate to the stripping agent is 1:0.6;
[0082] (2.2) The pH value of the reaction system was adjusted to 2 with an acid solution, and the mixture was centrifuged (at a speed of 6000 r / min) to remove the upper layer of liquid to obtain a translucent paste-like liquid;
[0083] (2.3) After adding deionized water to the translucent paste liquid, stirring, centrifuging, removing the upper liquid, repeating the above operation three times, and then performing rotary evaporation to obtain a paste with a water content of 12 wt%;
[0084] (2.4) Add the ethanol solution of silane coupling agent dropwise to the paste, react under stirring at 0.1 MPa and 40°C for 20 h, and obtain solid powder after post-treatment; wherein the mass of the silane coupling agent is 35% of the mass of the layered α-zirconium phosphate;
[0085] (2.5) dispersing the solid powder in an organic solvent to obtain a dispersion with a concentration of 8 wt %, adding a solution of unsaturated conjugated cross-linkable molecules containing benzene rings and a catalyst to the dispersion, reacting at 0.1 MPa and 25° C. for 12 h, and obtaining a highly efficient carbon-forming anti-melting droplet flame retardant through post-treatment; wherein the mass of the unsaturated conjugated cross-linkable molecules containing benzene rings is 30% of the mass of the layered α-zirconium phosphate, and the mass of the catalyst is 0.1% of the mass of the unsaturated conjugated cross-linkable molecules containing benzene rings;
[0086] The structural formula of the obtained high-efficiency carbon-forming anti-melting droplet flame retardant is ; The high-efficiency carbon-forming anti-melting-drip flame retardant is a monolayer α-zirconium phosphate with a width-to-thickness ratio of 520 and a surface grafted unsaturated conjugated crosslinkable molecule containing a benzene ring; the grafting rate of the unsaturated conjugated crosslinkable molecule containing a benzene ring on the monolayer α-zirconium phosphate is 38wt%; the initial thermal decomposition temperature of the high-efficiency carbon-forming anti-melting-drip flame retardant is 364℃, and an exothermic peak (395℃) appears between 350℃ and 400℃ on the DSC test curve;
[0087] (3) Preparation of highly efficient carbonized anti-melting droplet flame-retardant fibers;
[0088] (3.1) Firstly, the high-efficiency char-forming anti-melting-dropping flame retardant is melt-blended with the polymer powder to obtain a flame-retardant slice;
[0089] The tensile strength of the flame retardant slices was 54.2 MPa. Figure 1 As shown in the figure, the complex viscosity of the flame retardant slice at 370°C is 186 Pa·s. The complex viscosity between 300 and 350°C decreases slowly with increasing temperature. When the temperature reaches above 350°C, the complex viscosity increases rapidly with increasing temperature, making the fluidity worse, thereby achieving the purpose of anti-drip.
[0090] (3.2) The flame retardant slices are melt-spun to obtain high-efficiency carbon-forming anti-melt droplet flame retardant fibers; wherein, four pairs of drawing rollers are used for drawing during the melt spinning process, the temperature of the first pair of drawing rollers is 80°C, and the spinning speed is 600m / min; the temperature of the second pair of drawing rollers is 130°C, and the spinning speed is twice the spinning speed of the first pair of drawing rollers; the temperature of the third pair of drawing rollers is 180°C, and the spinning speed is 1.5 times the spinning speed of the second pair of drawing rollers; the temperature of the fourth pair of drawing rollers is 200°C, and the spinning speed is 1.2 times the spinning speed of the third pair of drawing rollers; the process parameters of melt spinning are: the temperature of zone 1 is 250°C, the temperature of zone 2 is 255°C, the temperature of zone 3 is 260°C, the temperature of zone 4 is 265°C, and the temperature of zone 5 is 260°C.
[0091] The high-efficiency carbon-forming anti-melting droplet flame-retardant fiber finally prepared is composed of a polymer matrix (i.e., polyester) and a high-efficiency carbon-forming anti-melting droplet flame retardant dispersed therein; the monolayer α-zirconium phosphate in the high-efficiency carbon-forming anti-melting droplet flame retardant is oriented along the axial direction of the fiber (e.g., Figure 2 As shown); the content of the high-efficiency charring anti-melting-drip flame retardant in the high-efficiency charring anti-melting-drip flame retardant fiber is 3wt%, the LOI of the high-efficiency charring anti-melting-drip flame retardant fiber is 34.5%, and the UL-94 reaches V0 grade.
[0092] Example 2
[0093] A method for preparing a highly efficient carbonized anti-melting droplet flame-retardant fiber, the specific steps are as follows:
[0094] (1) Preparation of raw materials;
[0095] Stripping agent solution: the solute is 4-amino-1-butanol, the solvent is deionized water, and the concentration is 10wt%;
[0096] Layered α-zirconium phosphate dispersion: The dispersed phase is layered α-zirconium phosphate (manufacturer is Changzhou Konada New Material Technology Co., Ltd., brand name is KND-SG300, average particle size is 2μm), the dispersion medium is deionized water, and the concentration is 10wt%;
[0097] Acid solution: nitric acid aqueous solution, concentration is 1 mol / L;
[0098] Deionized water;
[0099] Ethanol solution of silane coupling agent: the solute is γ-glycidyloxypropyltrimethoxysilane, the concentration is 10wt%;
[0100] Organic solvent: dichloromethane;
[0101] Unsaturated conjugated cross-linkable molecular solution containing benzene ring: the solute is 4,4'-diaminostilbene, the solvent is dichloromethane, and the concentration is 10wt%;
[0102] Catalyst: azobisisobutyronitrile;
[0103] Polymer chips: polyester, manufactured by Sinopec, brand FG720, tensile strength at break 55.8MPa;
[0104] Polymer powder: The polymer slices are pulverized by a high-speed pulverizer at a speed of 35000r / min for 2min to obtain polymer powder;
[0105] (2) Preparation of highly efficient carbon-forming anti-drip flame retardant;
[0106] (2.1) adding the stripping agent solution dropwise to the layered α-zirconium phosphate dispersion at a dropping speed of 1 second / drop, accompanied by mechanical stirring and ultrasound, and continuing to react after the dropping is completed until the pH value is 8; wherein the mass ratio of the layered α-zirconium phosphate to the stripping agent is 1:0.65;
[0107] (2.2) The pH value of the reaction system was adjusted to 2 with an acid solution, and the mixture was centrifuged (at a speed of 8000 r / min) to remove the upper layer of liquid to obtain a translucent paste-like liquid;
[0108] (2.3) After adding deionized water to the translucent paste liquid, stirring, centrifuging, removing the upper liquid, repeating the above operation three times, and then performing rotary evaporation to obtain a paste with a water content of 15wt%;
[0109] (2.4) Add the ethanol solution of silane coupling agent dropwise to the paste, react under stirring at 0.1 MPa and 55°C for 16 h, and obtain solid powder after post-treatment; wherein the mass of the silane coupling agent is 50% of the mass of the layered α-zirconium phosphate;
[0110] (2.5) dispersing the solid powder in an organic solvent to obtain a dispersion with a concentration of 8 wt %, adding a solution of unsaturated conjugated cross-linkable molecules containing benzene rings and a catalyst to the dispersion, reacting at 0.1 MPa and 60° C. for 10 h, and obtaining a highly efficient carbon-forming anti-melting droplet flame retardant through post-treatment; wherein the mass of the unsaturated conjugated cross-linkable molecules containing benzene rings is 45% of the mass of the layered α-zirconium phosphate, and the mass of the catalyst is 0.05% of the mass of the unsaturated conjugated cross-linkable molecules containing benzene rings;
[0111] The structural formula of the obtained high-efficiency carbon-forming anti-melting droplet flame retardant is ; The high-efficiency carbon-forming anti-melting-drip flame retardant is a monolayer α-zirconium phosphate with a width-to-thickness ratio of 550 and a surface grafted unsaturated conjugated crosslinkable molecule containing a benzene ring; the grafting rate of the unsaturated conjugated crosslinkable molecule containing a benzene ring on the monolayer α-zirconium phosphate is 60wt%; the initial thermal decomposition temperature of the high-efficiency carbon-forming anti-melting-drip flame retardant is 338℃, and an exothermic peak (356℃) appears between 350℃ and 400℃ on the DSC test curve;
[0112] (3) Preparation of highly efficient carbonized anti-melting droplet flame-retardant fibers;
[0113] (3.1) Firstly, the high-efficiency char-forming anti-melting-dropping flame retardant is melt-blended with the polymer powder to obtain a flame-retardant slice;
[0114] The tensile breaking strength of the flame-retardant slices was 56.5 MPa, and the complex viscosity at 370 °C was 182 Pa·s;
[0115] (3.2) The flame retardant slices are melt-spun to obtain high-efficiency carbon-forming anti-melt droplet flame retardant fibers; wherein, four pairs of drawing rollers are used for drawing during the melt spinning process, the temperature of the first pair of drawing rollers is 95°C, and the spinning speed is 650 m / min; the temperature of the second pair of drawing rollers is 135°C, and the spinning speed is 2.3 times the spinning speed of the first pair of drawing rollers; the temperature of the third pair of drawing rollers is 185°C, and the spinning speed is 1.4 times the spinning speed of the second pair of drawing rollers; the temperature of the fourth pair of drawing rollers is 220°C, and the spinning speed is 1 times the spinning speed of the third pair of drawing rollers; the process parameters of melt spinning are: the temperature of zone 1 is 255°C, the temperature of zone 2 is 260°C, the temperature of zone 3 is 260°C, the temperature of zone 4 is 270°C, and the temperature of zone 5 is 260°C.
[0116] The finally obtained high-efficiency charcoal-forming anti-drip flame-retardant fiber consists of a polymer matrix (i.e. polyester) and a high-efficiency charcoal-forming anti-drip flame retardant dispersed therein; the monolithic α-zirconium phosphate in the high-efficiency charcoal-forming anti-drip flame retardant is oriented along the axial direction of the fiber; the content of the high-efficiency charcoal-forming anti-drip flame retardant in the high-efficiency charcoal-forming anti-drip flame retardant is 2.5wt%, the LOI of the high-efficiency charcoal-forming anti-drip flame retardant fiber is 33.8%, and the UL-94 reaches V0 grade.
[0117] Example 3
[0118] A method for preparing a highly efficient carbonized anti-melting droplet flame-retardant fiber, the specific steps are as follows:
[0119] (1) Preparation of raw materials;
[0120] Stripping agent solution: the solute is 3-amino-1,2-propylene glycol, the solvent is deionized water, and the concentration is 10wt%;
[0121] Layered α-zirconium phosphate dispersion: The dispersed phase is layered α-zirconium phosphate (manufacturer is Fujian Ruisen New Materials Co., Ltd., brand name RS-LSG-C, average particle size is 2μm), the dispersion medium is deionized water, and the concentration is 10wt%;
[0122] Acid solution: phosphoric acid aqueous solution, concentration is 1 mol / L;
[0123] Deionized water;
[0124] Ethanol solution of silane coupling agent: the solute is γ-glycidyloxypropyltriethoxysilane, the concentration is 10wt%;
[0125] Organic solvent: acetone;
[0126] Unsaturated conjugated cross-linkable molecular solution containing benzene ring: the solute is 4-(benzylideneamino)aniline (CAS No. 7595-72-4), the solvent is acetone, and the concentration is 10wt%;
[0127] Catalyst: azobisisobutyronitrile;
[0128] Polymer slice: polyamide 6, manufactured by DuPont, USA, brand FG7301 NC010, tensile breaking strength 80.3MPa;
[0129] Polymer powder: The polymer slices are pulverized by a high-speed pulverizer at a speed of 35000r / min for 2min to obtain polymer powder;
[0130] (2) Preparation of highly efficient carbon-forming anti-drip flame retardant;
[0131] (2.1) adding the stripping agent solution dropwise to the layered α-zirconium phosphate dispersion at a dropping speed of 1 second / drop, accompanied by mechanical stirring and ultrasound, and continuing to react after the dropping is completed until the pH value is 8; wherein the mass ratio of the layered α-zirconium phosphate to the stripping agent is 1:0.72;
[0132] (2.2) The pH value of the reaction system was adjusted to 2 with an acid solution, and the mixture was centrifuged (at a speed of 8500 r / min) to remove the upper layer of liquid to obtain a translucent paste-like liquid;
[0133] (2.3) After adding deionized water to the translucent paste liquid, stirring, centrifuging, removing the upper liquid, repeating the above operation three times, and then performing rotary evaporation to obtain a paste with a water content of 13 wt%;
[0134] (2.4) Add the ethanol solution of silane coupling agent dropwise to the paste, react under stirring at 0.1 MPa and 80°C for 12 h, and obtain solid powder after post-treatment; wherein the mass of the silane coupling agent is 40% of the mass of the layered α-zirconium phosphate;
[0135] (2.5) dispersing the solid powder in an organic solvent to obtain a dispersion with a concentration of 9 wt%, adding a solution of unsaturated conjugated cross-linkable molecules containing benzene rings and a catalyst to the dispersion, reacting at 0.15 MPa and 60° C. for 8 h, and obtaining a highly efficient carbon-forming anti-melting droplet flame retardant through post-treatment; wherein the mass of the unsaturated conjugated cross-linkable molecules containing benzene rings is 50% of the mass of the layered α-zirconium phosphate, and the mass of the catalyst is 0.08% of the mass of the unsaturated conjugated cross-linkable molecules containing benzene rings;
[0136] The structural formula of the obtained high-efficiency carbon-forming anti-melting droplet flame retardant is ; The high-efficiency carbon-forming anti-melting-drip flame retardant is a monolayer α-zirconium phosphate with a width-to-thickness ratio of 580 and a surface grafted unsaturated conjugated crosslinkable molecule containing a benzene ring; the grafting rate of the unsaturated conjugated crosslinkable molecule containing a benzene ring on the monolayer α-zirconium phosphate is 42wt%; the initial thermal decomposition temperature of the high-efficiency carbon-forming anti-melting-drip flame retardant is 329℃, and an exothermic peak (363℃) appears between 350℃ and 400℃ on the DSC test curve;
[0137] (3) Preparation of highly efficient carbonized anti-melting droplet flame-retardant fibers;
[0138] (3.1) Firstly, the high-efficiency char-forming anti-melting-dropping flame retardant is melt-blended with the polymer powder to obtain a flame-retardant slice;
[0139] The tensile breaking strength of the flame-retardant slices was 85.7 MPa, and the complex viscosity at 370 °C was 225 Pa·s;
[0140] (3.2) The flame retardant slices are melt-spun to obtain high-efficiency carbon-forming anti-melt droplet flame retardant fibers; wherein, four pairs of drawing rollers are used for drawing during the melt spinning process, the temperature of the first pair of drawing rollers is 108°C, and the spinning speed is 650 m / min; the temperature of the second pair of drawing rollers is 145°C, and the spinning speed is 2.2 times the spinning speed of the first pair of drawing rollers; the temperature of the third pair of drawing rollers is 195°C, and the spinning speed is 1.5 times the spinning speed of the second pair of drawing rollers; the temperature of the fourth pair of drawing rollers is 230°C, and the spinning speed is 1 times the spinning speed of the third pair of drawing rollers; the process parameters of melt spinning are: the temperature of zone 1 is 260°C, the temperature of zone 2 is 265°C, the temperature of zone 3 is 265°C, the temperature of zone 4 is 270°C, and the temperature of zone 5 is 265°C.
[0141] The finally obtained high-efficiency charcoal-forming anti-drip flame-retardant fiber consists of a polymer matrix (i.e., polyamide 6) and a high-efficiency charcoal-forming anti-drip flame retardant dispersed therein; the monolithic α-zirconium phosphate in the high-efficiency charcoal-forming anti-drip flame retardant is oriented along the axial direction of the fiber; the content of the high-efficiency charcoal-forming anti-drip flame retardant in the high-efficiency charcoal-forming anti-drip flame retardant is 2wt%, the LOI of the high-efficiency charcoal-forming anti-drip flame retardant fiber is 33.2%, and the UL-94 reaches V0 grade.
[0142] Example 4
[0143] A method for preparing a highly efficient carbonized anti-melting droplet flame-retardant fiber, the specific steps are as follows:
[0144] (1) Preparation of raw materials;
[0145] Stripping agent solution: the solute is tetrabutylammonium hydroxide, the solvent is deionized water, and the concentration is 10wt%;
[0146] Layered α-zirconium phosphate dispersion: The dispersed phase is layered α-zirconium phosphate (manufacturer is Fujian Ruisen New Materials Co., Ltd., brand name RS-LSG-C, average particle size is 2μm), the dispersion medium is deionized water, and the concentration is 12wt%;
[0147] Acid solution: hydrochloric acid aqueous solution, concentration is 1 mol / L;
[0148] Deionized water;
[0149] Ethanol solution of silane coupling agent: the solute is γ-aminopropyltrimethoxysilane, the concentration is 10wt%;
[0150] Organic solvent: dimethyl sulfoxide;
[0151] Unsaturated conjugated cross-linkable molecular solution containing benzene ring: the solute is 3,3',5,5'-azobenzenetetracarboxylic acid, the solvent is dimethyl sulfoxide, and the concentration is 13wt%;
[0152] Catalyst: toluenesulfonic acid;
[0153] Polymer slice: polyamide 6, manufactured by DuPont, USA, brand 7304 NC010, tensile breaking strength 74.2MPa;
[0154] Polymer powder: The polymer slices are pulverized by a high-speed pulverizer at a speed of 35000r / min for 2min to obtain polymer powder;
[0155] (2) Preparation of highly efficient carbon-forming anti-drip flame retardant;
[0156] (2.1) adding the stripping agent solution dropwise to the layered α-zirconium phosphate dispersion at a dropping speed of 2 seconds per drop, accompanied by mechanical stirring and ultrasound, and continuing to react after the dropping is completed until the pH value is 7.5; wherein the mass ratio of the layered α-zirconium phosphate to the stripping agent is 1:0.8;
[0157] (2.2) The pH value of the reaction system was adjusted to 3 with an acid solution, and the mixture was centrifuged (at a speed of 9500 r / min) to remove the upper layer of liquid to obtain a translucent paste-like liquid;
[0158] (2.3) After adding deionized water to the translucent paste liquid, stirring, centrifuging, removing the upper liquid, repeating the above operation three times, and then performing rotary evaporation to obtain a paste with a water content of 14 wt%;
[0159] (2.4) Add the ethanol solution of silane coupling agent dropwise to the paste, react under stirring at 0.1 MPa and 25°C for 24 hours, and obtain solid powder after post-treatment; the mass of the silane coupling agent is 45% of the mass of the layered α-zirconium phosphate;
[0160] (2.5) dispersing the solid powder in an organic solvent to obtain a dispersion with a concentration of 9 wt%, adding a solution of unsaturated conjugated cross-linkable molecules containing benzene rings and a catalyst to the dispersion, reacting at 0.12 MPa and 120° C. for 3 h, and obtaining a highly efficient carbon-forming anti-melting droplet flame retardant through post-treatment; wherein the mass of the unsaturated conjugated cross-linkable molecules containing benzene rings is 30% of the mass of the layered α-zirconium phosphate, and the mass of the catalyst is 0.1% of the mass of the unsaturated conjugated cross-linkable molecules containing benzene rings;
[0161] The structural formula of the obtained high-efficiency carbon-forming anti-melting droplet flame retardant is ; The high-efficiency carbon-forming anti-melting-drip flame retardant is a monolayer α-zirconium phosphate with a width-to-thickness ratio of 600 and a surface grafted unsaturated conjugated crosslinkable molecule containing a benzene ring; the grafting rate of the unsaturated conjugated crosslinkable molecule containing a benzene ring on the monolayer α-zirconium phosphate is 30wt%; the initial thermal decomposition temperature of the high-efficiency carbon-forming anti-melting-drip flame retardant is 352℃, and an exothermic peak (372℃) appears between 350℃ and 400℃ on the DSC test curve;
[0162] (3) Preparation of highly efficient carbonized anti-melting droplet flame-retardant fibers;
[0163] (3.1) Firstly, the high-efficiency char-forming anti-melting-dropping flame retardant is melt-blended with the polymer powder to obtain a flame-retardant slice;
[0164] The tensile breaking strength of the flame-retardant slices was 75.8 MPa, and the complex viscosity at 370 °C was 213 Pa·s;
[0165] (3.2) The flame retardant slices are melt-spun to obtain high-efficiency carbon-forming anti-melt droplet flame retardant fibers; wherein, four pairs of drawing rollers are used for drawing during the melt spinning process, the temperature of the first pair of drawing rollers is 120°C, and the spinning speed is 700 m / min; the temperature of the second pair of drawing rollers is 150°C, and the spinning speed is 2.5 times the spinning speed of the first pair of drawing rollers; the temperature of the third pair of drawing rollers is 200°C, and the spinning speed is 1.3 times the spinning speed of the second pair of drawing rollers; the temperature of the fourth pair of drawing rollers is 240°C, and the spinning speed is 1.1 times the spinning speed of the third pair of drawing rollers; the process parameters of melt spinning are: the temperature of zone 1 is 260°C, the temperature of zone 2 is 265°C, the temperature of zone 3 is 265°C, the temperature of zone 4 is 270°C, and the temperature of zone 5 is 265°C.
[0166] The finally obtained high-efficiency charcoal-forming anti-drip flame-retardant fiber consists of a polymer matrix (i.e., polyamide 6) and a high-efficiency charcoal-forming anti-drip flame retardant dispersed therein; the monolithic α-zirconium phosphate in the high-efficiency charcoal-forming anti-drip flame retardant is oriented along the axial direction of the fiber; the content of the high-efficiency charcoal-forming anti-drip flame retardant in the high-efficiency charcoal-forming anti-drip flame retardant is 1wt%, the LOI of the high-efficiency charcoal-forming anti-drip flame retardant fiber is 32.6%, and the UL-94 reaches V0 grade.
[0167] Comparative Example 1
[0168] A method for preparing a flame-retardant fiber is basically the same as that in Example 4, except that: the manufacturer of the layered α-zirconium phosphate in the raw material is Shanghai Runhe Nanomaterial Technology Co., Ltd., the brand is RHA-ZRF, and the average particle size is 1 μm, which results in the width-to-thickness ratio of the flame retardant being less than 500, which in turn results in the single-layer α-zirconium phosphate in the flame retardant in the final flame-retardant fiber being unable to be oriented along the axial direction of the fiber, which is not conducive to the α-zirconium phosphate exerting its flame retardant function; tests show that the LOI of the flame-retardant fiber is 28.8%, and the UL-94 reaches the V-1 level. By comparison, it can be seen that the flame retardant performance of the flame-retardant fiber of Comparative Example 1 is significantly lower than that of Example 4, which supports the above viewpoint.
[0169] Comparative Example 2
[0170] A method for preparing a flame-retardant fiber is basically the same as that in Example 4, except that: the temperature of the first pair of drafting rollers is 75°C, the temperature of the second pair of drafting rollers is 120°C, the temperature of the third pair of drafting rollers is 150°C, and the temperature of the fourth pair of drafting rollers is 200°C, which results in that the disorderly dispersed single-layer α-zirconium phosphate in the fiber cannot be fully oriented under the induction of drafting to form an ordered directional arrangement structure, which is not conducive to the α-zirconium phosphate to exert its flame retardant function; tests show that the LOI of the flame-retardant fiber is 29.2%, and the UL-94 reaches the V-1 level. By comparison, it can be seen that the flame retardant performance of the flame-retardant fiber of Comparative Example 2 is significantly lower than that of Example 4, which confirms the above view.
[0171] Comparative Example 3
[0172] A method for preparing a flame retardant fiber is basically the same as that in Example 4, except that: step (2.5) is: dispersing a solid powder in an organic solvent to obtain a dispersion having a concentration of 9 wt%, adding a catalyst (the type and amount are the same as in Example 4) to the dispersion, reacting at 0.12 MPa and 120° C. for 3 h, performing post-treatment, mixing the product obtained by the post-treatment with an unsaturated conjugated cross-linkable molecule containing a benzene ring (the type and amount are the same as in Example 4), and obtaining a flame retardant; due to the unsaturated conjugated cross-linkable molecule containing a benzene ring The conjugated cross-linkable molecules are not grafted onto the monolithic α-zirconium phosphate, but are only mixed with the monolithic α-zirconium phosphate, resulting in the cross-linking points of the unsaturated conjugated cross-linkable molecules containing benzene rings not being on the surface of the monolithic α-zirconium phosphate at high temperatures. The synergistic effect of the flame retardant and anti-melting droplet properties of the two is weakened, and the flame retardant and anti-melting droplet properties are reduced. Tests show that the LOI of the flame retardant fiber is 30.7%, and the UL-94 reaches the V-0 grade. By comparison, it can be seen that the flame retardant performance of the flame retardant fiber of Comparative Example 3 is significantly lower than that of Example 4, which confirms the above view.
[0173] Example 5
[0174] A method for preparing a highly efficient carbonized anti-melting droplet flame-retardant fiber, the specific steps are as follows:
[0175] (1) Preparation of raw materials;
[0176] Stripping agent solution: the solute is tromethamine, the solvent is deionized water, and the concentration is 10wt%;
[0177] Layered α-zirconium phosphate dispersion: The dispersed phase is layered α-zirconium phosphate (manufacturer is Shanghai Runhe Nanomaterial Technology Co., Ltd., brand name is RHA-ZR, average particle size is 2μm), the dispersion medium is deionized water, and the concentration is 15wt%;
[0178] Acid solution: nitric acid aqueous solution, concentration is 1 mol / L;
[0179] Deionized water;
[0180] Ethanol solution of silane coupling agent: the solute is N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane, and the concentration is 10wt%;
[0181] Organic solvent: DMF;
[0182] Unsaturated conjugated cross-linkable molecular solution containing benzene ring: the solute is p-aminoazophenyl-4-sulfonic acid, the solvent is DMF, and the concentration is 15wt%;
[0183] Catalyst: 1,3-dicyclohexylcarbodiimide;
[0184] Polymer chips: polyester, manufactured by Sinopec, brand FG720, tensile strength at break 55.8MPa;
[0185] Polymer powder: The polymer slices are pulverized by a high-speed pulverizer at a speed of 35000r / min for 2min to obtain polymer powder;
[0186] (2) Preparation of highly efficient carbon-forming anti-drip flame retardant;
[0187] (2.1) adding the stripping agent solution dropwise to the layered α-zirconium phosphate dispersion at a dropping speed of 2 seconds per drop, accompanied by mechanical stirring and ultrasound, and continuing to react after the dropping is completed until the pH value is 7; wherein the mass ratio of the layered α-zirconium phosphate to the stripping agent is 1:0.62;
[0188] (2.2) The pH value of the reaction system was adjusted to 3 with an acid solution, and the mixture was centrifuged (at a speed of 10,000 r / min) to remove the upper layer of liquid to obtain a translucent paste-like liquid;
[0189] (2.3) After adding deionized water to the translucent paste liquid, stirring, centrifuging, removing the upper liquid, repeating the above operation three times, and then performing rotary evaporation to obtain a paste with a water content of 10 wt%;
[0190] (2.4) Add the ethanol solution of silane coupling agent dropwise to the paste, react under stirring at 0.1 MPa and 70°C for 12 h, and obtain solid powder after post-treatment; wherein the mass of the silane coupling agent is 30% of the mass of the layered α-zirconium phosphate;
[0191] (2.5) dispersing the solid powder in an organic solvent to obtain a dispersion with a concentration of 10 wt%, adding a solution of unsaturated conjugated cross-linkable molecules containing benzene rings and a catalyst to the dispersion, reacting at 0.1 MPa and 120° C. for 6 h, and obtaining a highly efficient carbon-forming anti-melting droplet flame retardant through post-treatment; wherein the mass of the unsaturated conjugated cross-linkable molecules containing benzene rings is 60% of the mass of the layered α-zirconium phosphate, and the mass of the catalyst is 0.1% of the mass of the unsaturated conjugated cross-linkable molecules containing benzene rings;
[0192] The structural formula of the obtained high-efficiency carbon-forming anti-melting droplet flame retardant is ; The high-efficiency carbon-forming anti-melting-drip flame retardant is a monolayer α-zirconium phosphate with a width-to-thickness ratio of 600 and a surface grafted unsaturated conjugated crosslinkable molecule containing a benzene ring; the grafting rate of the unsaturated conjugated crosslinkable molecule containing a benzene ring on the monolayer α-zirconium phosphate is 54wt%; the initial thermal decomposition temperature of the high-efficiency carbon-forming anti-melting-drip flame retardant is 313℃, and an exothermic peak (359℃) appears between 350℃ and 400℃ on the DSC test curve;
[0193] (3) Preparation of highly efficient carbonized anti-melting droplet flame-retardant fibers;
[0194] (3.1) Firstly, the high-efficiency char-forming anti-melting-dropping flame retardant is melt-blended with the polymer powder to obtain a flame-retardant slice;
[0195] The tensile breaking strength of the flame-retardant slices was 57.3 MPa, and the complex viscosity at 370 °C was 188 Pa·s;
[0196] (3.2) The flame retardant slices are melt-spun to obtain high-efficiency carbon-forming anti-melt droplet flame retardant fibers; wherein, four pairs of drawing rollers are used for drawing during the melt spinning process, the temperature of the first pair of drawing rollers is 90°C, and the spinning speed is 600m / min; the temperature of the second pair of drawing rollers is 135°C, and the spinning speed is twice the spinning speed of the first pair of drawing rollers; the temperature of the third pair of drawing rollers is 195°C, and the spinning speed is 1.5 times the spinning speed of the second pair of drawing rollers; the temperature of the fourth pair of drawing rollers is 210°C, and the spinning speed is 1.1 times the spinning speed of the third pair of drawing rollers; the process parameters of melt spinning are: the temperature of zone 1 is 250°C, the temperature of zone 2 is 255°C, the temperature of zone 3 is 260°C, the temperature of zone 4 is 265°C, and the temperature of zone 5 is 260°C.
[0197] The finally obtained high-efficiency charcoal-forming anti-drip flame-retardant fiber consists of a polymer matrix (i.e. polyester) and a high-efficiency charcoal-forming anti-drip flame retardant dispersed therein; the monolithic α-zirconium phosphate in the high-efficiency charcoal-forming anti-drip flame retardant is oriented along the axial direction of the fiber; the content of the high-efficiency charcoal-forming anti-drip flame retardant in the high-efficiency charcoal-forming anti-drip flame retardant is 2wt%, the LOI of the high-efficiency charcoal-forming anti-drip flame retardant fiber is 34.1%, and the UL-94 reaches V0 grade.
Claims
1. A method for preparing a highly efficient carbonized anti-drip flame-retardant fiber, characterized in that: The flame retardant slices are melt-spun, and four pairs of drafting rollers are used for drafting during the melt spinning process. The temperature of the first pair of drafting rollers is 80-120°C, the temperature of the second pair of drafting rollers is 130-150°C, the temperature of the third pair of drafting rollers is 180-200°C, the temperature of the fourth pair of drafting rollers is 200-240°C, and the total drafting multiple is 4.5-5.0, so as to obtain a high-efficiency carbon-forming anti-melting droplet flame retardant fiber; The high-efficiency carbon-forming anti-melting-drip flame-retardant fiber is composed of a polymer matrix and a high-efficiency carbon-forming anti-melting-drip flame retardant dispersed therein; the monolayer α-zirconium phosphate in the high-efficiency carbon-forming anti-melting-drip flame retardant is oriented along the axial direction of the fiber; The highly efficient carbon-forming anti-melting drop flame retardant is a monolayer α-zirconium phosphate with a width-to-thickness ratio greater than 500 and a surface grafted unsaturated conjugated crosslinkable molecule containing a benzene ring; The structural formula of the unsaturated conjugated cross-linkable molecule containing a benzene ring is as follows: or ; In the formula, -R- is -CH=CH-, -C≡C-, -CH=N- or -N=N-; at least one of -R1 to -R6 is an active functional group, which is -NH2, -COOH or -SO3H, and the rest are -H; By using a silane coupling agent to graft unsaturated conjugated crosslinkable molecules containing benzene rings onto a monolayer of α-zirconium phosphate, a highly efficient carbon-forming anti-melting droplet flame retardant is obtained. The preparation steps of the high-efficiency carbon-forming anti-drip flame retardant are as follows: (1) using a stripping agent to strip the layered α-zirconium phosphate in a solvent to obtain a paste consisting of a single layer of α-zirconium phosphate and a solvent; (2) adding the ethanol solution of the silane coupling agent dropwise to the paste, reacting under stirring at 0.1 MPa and 25-80°C for 12-24 hours, and obtaining a solid powder through post-treatment; (3) The solid powder is dispersed in an organic solvent to obtain a dispersion, and an unsaturated conjugated cross-linkable molecular solution containing a benzene ring and a catalyst are added to the dispersion, and the dispersion is reacted at 0.1-0.15 MPa and 25-120° C. for 3-12 hours. After post-treatment, a highly efficient carbon-forming anti-dripping flame retardant is obtained.
2. The method for preparing a highly efficient carbonized anti-drip flame-retardant fiber according to claim 1, characterized in that: The spinning speed of the first pair of drafting rollers is 600-700 m / min, the spinning speed of the second pair of drafting rollers is 2.0-2.5 times that of the first pair of drafting rollers, the spinning speed of the third pair of drafting rollers is 1.3-1.5 times that of the second pair of drafting rollers, and the spinning speed of the fourth pair of drafting rollers is 1.0-1.2 times that of the third pair of drafting rollers; The preparation process of the flame retardant slices is as follows: first, a high-efficiency char-forming anti-drip flame retardant is melt-blended with a polymer powder to obtain a flame retardant slice. The polymer powder and the polymer slices are made of the same material. The prepared flame retardant slices have a tensile breaking strength of 54.2~85.7MPa and a complex viscosity of 182~225Pa·s at 370°C.
3. The method for preparing a highly efficient carbonized anti-drip flame-retardant fiber according to claim 1, characterized in that: The grafting rate of unsaturated conjugated cross-linkable molecules containing benzene rings on a single layer of α-zirconium phosphate is 30~60wt%.
4. The method for preparing a highly efficient carbonized anti-drip flame-retardant fiber according to claim 1, characterized in that: The initial thermal decomposition temperature of the high-efficiency char-forming anti-drip flame retardant is >300°C, and an exothermic peak appears between 350°C and 400°C on the DSC test curve.
5. The method for preparing a highly efficient carbonized anti-drip flame-retardant fiber according to claim 1, characterized in that: Step (1) is as follows: (1.1) Add the stripping agent solution dropwise into the layered α-zirconium phosphate dispersion at a dropping speed of 1 to 2 seconds per drop, accompanied by mechanical stirring and ultrasound, and continue to react until the pH value reaches 7 to 8 after the dropping is completed; The stripping agent is one or more of D-aminopropanol, 4-amino-1-butanol, 2-aminocyclohexanol, 6-amino-1-hexanol, 3-aminobutanol, 3-amino-1,2-propylene glycol, tromethamine, tetrabutylammonium hydroxide, and hexadecyltrimethylammonium hydroxide; The concentration of the stripping agent solution is 10wt%, and the solvent is deionized water; The average particle size of the layered α-zirconium phosphate is 2 μm; The concentration of the layered α-zirconium phosphate dispersion is 10-15 wt %, and the solvent is deionized water; The mass ratio of layered α-zirconium phosphate to stripping agent is 1:0.6~0.8; (1.2) Adjust the pH value of the reaction system to 2-3 with an acid solution, centrifuge, remove the upper liquid, and obtain a translucent paste-like liquid; The acid solution is a hydrochloric acid aqueous solution, a nitric acid aqueous solution or a phosphoric acid aqueous solution; (1.3) After adding deionized water to the translucent paste liquid, stirring, centrifuging, removing the upper liquid, repeating the above operation 3 times, and then performing rotary evaporation to obtain a paste with a water content of 10-15wt%; In step (2), the concentration of the ethanol solution of the silane coupling agent is 10 wt %, and the mass of the silane coupling agent is 30-50% of the mass of the layered α-zirconium phosphate; In step (3), the concentration of the dispersion is 8-10 wt %, and the organic solvent is toluene, dichloromethane, chloroform, acetone, dimethyl sulfoxide or DMF; The concentration of the solution of the unsaturated conjugated crosslinkable molecule containing a benzene ring is 10-20wt%, the solvent is toluene, dichloromethane, chloroform, acetone, dimethyl sulfoxide or DMF, and the mass of the unsaturated conjugated crosslinkable molecule containing a benzene ring is 30-60% of the mass of the layered α-zirconium phosphate; The catalyst is azobisisobutyronitrile, 1,3-dicyclohexylcarbodiimide or p-toluenesulfonic acid, and the mass of the catalyst is 0.05-0.1% of the mass of the unsaturated conjugated cross-linkable molecule containing a benzene ring.
6. The method for preparing a highly efficient carbonized anti-drip flame-retardant fiber according to claim 1, characterized in that: The polymer matrix is polyester; the content of the high-efficiency carbon-forming anti-melting droplet flame retardant in the high-efficiency carbon-forming anti-melting droplet flame retardant fiber is 1-3wt%, the LOI of the high-efficiency carbon-forming anti-melting droplet flame retardant fiber is >32%, and the UL-94 reaches V0 grade; Alternatively, the polymer matrix is polyamide; the content of the high-efficiency charring anti-melting droplet flame retardant in the high-efficiency charring anti-melting droplet flame retardant fiber is 1-3wt%, the LOI of the high-efficiency charring anti-melting droplet flame retardant fiber is greater than 32%, and the UL-94 reaches V0 grade.
Citation Information
Patent Citations
Washable flame-retardant anti-dripping polyester cotton 65 / 35 fabric and preparation method thereof
CN116427173A
Modified POSS (Polyhedral Oligomeric Silsesquioxane) flame retardant as well as preparation method and application thereof in regenerated polyester
CN116693859A
High-temperature-resistant flame-retardant polyester fiber and preparation process thereof
CN116770453A
Cage molecule-containing flame retardant, preparation method thereof and application of cage molecule-containing flame retardant in regenerated products
CN116813909A
Preparation method of flame-retardant molten-drop-inhibiting polyester fiber
CN117210956A